COMMUNICATION STRATEGIES USED BY ENGLISH EDUCATION DEPARTMENT STUDENTS OF DWIJENDRA UNIVERSITY IN LEARNING PROCESS - Triana Juliari, I Gusti Ayu Indah (Widya Accarya, 2018)
ABSTRAKTujuan dari penelitian ini adalah untuk menginvestigasi strategi â?? strategi berkomunikasi yang digunakan olehÂ  mahasiswa Program Studi Pendidikan Bahasa Inggris dalam proses pembelajaran. Penelitian ini fokus pada jenis â?? jenis dan alasan siswa menggunakan strategi â?? strategi berkomunikasi. Subjek dari penelitian ini adalah mahasiswa semester lima Program Studi Pendidikan Bahasa Inggris Universitas Dwijendra. Dalam mengumpulkan data, peneliti menggunakan beberapa instrumen â?? instrumen, antara lain lembar observasi, catatan lapangan, dan pedoman wawancara. Jenis â??jenis dari strategi berkomunikasi dikumpulkan melalui melakukan observasi dan mencatat hal â?? hal penting yang terjadi pada proses pembelajaran, sementara itu metode wawancara digunakan untuk mengetahui alasan Mahasiswa dalam menggunakan strategi â?? strategi tersebut dalam proses pembelajaran. Hasil dari penelitian ini menujukkan bahwa ada 8 jenis strategi â?? strategi berkomunikasi yang digunakan oleh Mahasiswa Program Studi Pendidikan Bahasa Inggris. Strategi â?? strategi tersebut adalah message abandonment dari avoidance strategies, approximation, literal translation, code switching, and stalling or time gaining from compensatory strategies, appeal for assistance and non-linguistic signals/mime from conscious transfer, and asking for repetition of interactional strategy. Stalling or time gaining strategi merupakan strategi yang paling sering digunakan oleh Mahasiswa. Strategi tersebut terjadi sebanyak 12 kali di dalam proses pembelajaran. Alasan mahasiswa menngunakan strategi â??strategi tersebut karena mereka tidak tahu beberapa kata dalam bahasa Inggris dan agar teman â?? temannya mengerti tentang topic yang sedang didiskusikan.Kata Kunci: Strategi - strategi Berkomunikasi, Pelajar bahasa Inggris sebagai bahasa asing, Pengajaran Bahasa Inggris, Proses Pembelajaran ABSTRACTThe purpose of this research is to investigate Communication Strategies used by English Education Department Students Dwijendra University in learning process. It focuses on types and the students reasons toward the use of Communication Strategies. The subjects of this research were the fifth semester of English Education Department Students at Dwijendra University. In collecting the data, the researcher used some instruments, namely: observation sheet, field note, and interview guide. The types of Communication Strategies were gathered by observing and take note for the important thing in learning process, while the interview method was used to know the studentsâ?? reason in using those strategies in learning process. Â The results of this research showed that there were 8 types of Communication Strategies used by English Education Department Students. Those strategies were message abandonment from avoidance strategies, approximation, literal translation, code switching, and stalling or time gaining from compensatory strategies, appeal for assistance and non-linguistic signals/mime from Conscious transfer, and asking for repetition of interactional strategy. Stalling or time gaining strategy was the most frequently used by the students. It occurred for 12 times in learning process. The reasons of the students used those strategies because they do not know the English of certain words and in order to make their friends understand about the topic being discussed.Keywords: Communication Strategies, EFL, English Language Teaching, Learning Process